Culture, creativity, and conceptual dynamics: A structural hypothesis - Per Aage Brandt (Globe, 2015)
We redefine the concept of concept and focus on its role in the intersubjective processes that characterize cultures and socio-cultural communities. Conceptual density determines communitary coherence, whereas highly variable conceptual velocity determines inter-conceptual dynamics within distinct conceptual fields of activity. Conflicts opposing force of conceptual authority by knowledge value and force of conceptual authority through social power lead to states of socio-cultural consensus or dissensus. A model of socio-cultural concept structure is proposed. The creativity of concept formation is considered a major factor in historical time; different states of relative balance between creativity and stereotypicity are mentioned, including a dangerous neutralizing alliance of artistic and epistemic creativity on the one hand and technologically enhanced power concepts. In a sense, thinking is ubiquitous, but only certain forms of thinking are creative – those that minimize the influence of social power and maximize the slow intersubjective processes of shared experience that make culture be culture.